Kemampuan Induktansi pada Material Inti Logam Induktor Besi Cor ASTM A48, Nichrome dan Monel Alloy 400 Terhadap Variasi Input Listrik dan Lilitan - Vera Pangni Fahriani; Reza Setiawan; Suciani Rahma Pertiwi (Jurnal Serambi Engineering, 2021)
Inductor with a metal core is a component which  is almost always present in the daily  electronic device known to us . To further prove the potential  of the proposed new metalcore material, it is necessary to test the voltage variation, winding, and frequency in the inductor with the newly proposed metallic core material. The research method uses experimental methods. Three basic metal materials were used in the experiment, those are Cast Iron ASTM A48 (C 3.4%, Mn 0.5%, Si 1.8%,), Nicromine (Ni 80%, Cr 20%), Monel Alloy 400 (Ni 63%, Cu 31.7%, C 0.3%, Fe 2.5%, Si 0.5%, Mn 2%, S 0.024%). Experimental tests on these new types of metal were also carried out under various stress, winding, and working frequency conditions. The voltage variation selected is 4.5 V - 24 V,  the winding variations and frequencies selected are 150 to  1000 turns and 50 Hz. The  greatest inductance was obtained from ASTM A48, Fe, Monel Alloy 400, Nikromic, and without metallic core on the specified indicator variables. As the voltage increases and the number of turns increases,  the inductance value increases.